2014
DOI: 10.1007/s10633-014-9457-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing enfant and PowerDiva sweep visual evoked potential (sVEP) acuity estimates

Abstract: Acuity estimates with the Enfant and PowerDiva are not significantly different for patients with normal acuity. Thus, direct comparisons between the two instruments can be made for patients with normal acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It then linearly increased from a ratio of 1.1 (i.e., eleven items) to a ratio of 1.5 (i.e., fifteen items) with an incremental step of 0.1. This increasing fluctuation within a single stimulation sequence is based on the sweep visual evoked potential technique 32 , 56 59 .…”
Section: Methodsmentioning
confidence: 99%
“…It then linearly increased from a ratio of 1.1 (i.e., eleven items) to a ratio of 1.5 (i.e., fifteen items) with an incremental step of 0.1. This increasing fluctuation within a single stimulation sequence is based on the sweep visual evoked potential technique 32 , 56 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Where SFs viewed or available extend to finer values than the VEP SF limit, i.e. bracket the electrophysiological limit and presumably eliminate the possibility of a ceiling effect, average VEP SF limits are slightly higher [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Several studies give examples of individuals with VEP SF limits of C 40 cpd [12,18,19,[34][35][36][37] suggesting this as a suitable upper limit for subjects where a normal VEP SF limit is possible.…”
Section: Vep Sf Limits In Normally Sighted Adultsmentioning
confidence: 99%
“…To obtain better VEP results, preferably, most of the sweep spatial frequencies should be recognizable with a significant SNR to extrapolate the amplitude against spatial frequency. The sweep range of spatial frequency is about 3 to 30 cpd, corresponding to psychophysical optotypes from 1.0 to 0.0 logMAR in normal humans [ 7 , 36 , 77 , 83 , 85 , 87 , 97 , 98 ]. Besides, the sweep range was biased toward lower spatial frequencies in studies on infants and depended on their age, since their visual function develops over time [ 13 , 19 , 20 , 52 , 65 , 66 , 81 , 88 , 99 , 100 , 101 ].…”
Section: Effects Of Visual Stimulimentioning
confidence: 99%
“…Bach and Farmer [ 26 ] evaluated the implementation and outcome quality of the VEP acuity method on commercial equipment (Diagnosys Espion Profile and E3 electrophysiology systems) and found that VEP acuity agreed with subjective acuity to within ± 0.31 logMAR, indicating that this technique can be accessible to more users. In addition, Ridder et al [ 97 ] compared the two commonly used systems, Enfant and PowerDiva, demonstrating that the acuity estimates with these systems did not have significant differences for normal subjects.…”
Section: Effects Of Signal Acquisition and Analysismentioning
confidence: 99%